On Some Types Of N-functions - Dr. Sattar Hameed Hamzah Al-Janabi (Al-Qadisiyah Journal of Pure Science, 2017)
In this work ,we introduce the definitions of some types of N-functionsnamely N-irresolute, strongly N-closed and N-perfect, and investigate the propertiesof composition, restrictions and product of each type. Also, we give the relationamong them.